EFEKTIFITAS METODE MENGAJAR KESELURUHAN DENGAN METODE MENGAJAR BAGIAN PERBAGIAN TERHADAP HASIL BELAJAR MENGUMPAN (PASSING) KAKI BAGIAN DALAM PADA PERMAINAN FUTSAL MAHASISWA FIK UNM - Sudirman, Sudirman; Jaya, Andi Mas (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2020)
This study aims to find out which is more effective between the overall method and the teaching method part by section on learning outcomes passing (passing) the inner leg in students who take Futsal learning. This research was carried out by an experimental method in total sampling. Thedata analysis technique used to test the hypothesis is the t-test, at a significant level Î±= 0.05, starting with calculating the t-count value to compare with the t-table value at a significant level of 95%. (1) The whole method is obtained by t-count = 4, the value listed in t-table with degrees of freedom (dk) = 15-1 = 14. A significant level of 5% is 2.14, so t-count> t-table, means that there is a convincing (significant) difference before and after being given the overall method treatment. (2) The teaching method part of division is obtained the value of t-count = 3.7, the value listed in t-table with degrees of freedom (dk) = 15-1 = 14. Significant level of 5% is 2.14, so t-count> t-table, means that there is a convincing (significant) difference before and after the treatment method is given in part. And (3) The overall method and the part-by-part teaching method obtained t-count = 3.2, the values listed in t-table with degrees of freedom (dk) = 15 + 15-2 = 28. A significant level of 5% is 2.05. So t-count> t-table.